Syncopations : the stress of innovation in contemporary American poetry - Rasula, Jed. (Tuscaloosa : University of Alabama Press, 2004)
Makes a case for innovation as the generative and thematic force in American poetry of the late 20th century. Syncopations is an analysis of the sustaining vitality behind contemporary American poetry from 1975 to the present day by one of the most astute observers and critics in the field. The 12 essays reflect Jed Rasula's nearly 30 years of advocacy on behalf of "opening the field" of American poetry. From the Beats and the Black Mountain poets in the 1950s and 1960s to the impact of language poetry, the specter of an avant-garde has haunted the administrative centers of poetic co
List of Illustrations; Preface; Introduction; 1. Women, Innovation, and "Improbable Evidence"; 2. Seeing Double: The Grapes of Dysraphism; 3. News and Noise: Poetry and Distortion; 4. The Catastrophe of Charm; 5. Literacy Effects: Handling the Fiction, Nursing the Wounds; 6. Ethnopoetics and the Pathology of Modernism; 7. Every Day Another Vanguard; 8. Experiment as a Claim of the Book: Twenty Different Fruits on One Different Tree; 9. To Moisten the Atmosphere: Notes on Clayton Eshleman; 10. "Riddle Iota Sublime": Ronald Johnson's ARK.
Includes bibliographical references (pages 291-304) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: American poetry -- 20th century -- History and criticism; Experimental poetry, American -- History and criticism; Poésie américaine -- 20e siècle -- Histoire et critique; Poésie expérimentale américaine -- Histoire et critique; POETRY -- American -- General; American poetry; Experimental poetry, American; 1900-1999; Criticism, interpretation, etc